Little Blue and Little Yellow : A Story for Pippo and Ann and Other Children - Lionni, Leo 1910-1999. (New York : Alfred A. Knopf, 2009)
A little blue spot and a little yellow spot are best friends, and when they hug each other they become green.
"Originally published by McDowell Obolensky, Inc., New York, in 1959"--T.p. verso.
Edition statement from cover.
Keywords: Color -- Fiction; Friendship -- Fiction